CMLHS Researchers Shined their Stars at CITREX 2019 - Ezihaslinda, Ngah (2019)
15th February 2019, Gambang- Centre for Modern Languages and Human Sciences had successfully participated in the ninth Creation, Innovation, Technology and Research Exposition (CIREX) 2019. CITREX 2019 was held for two consecutive days on 12th- 13th February 2019 invited all researchers from all over the country to showcase their research products at the exhibition as the platform to gain not only recognition from credible judges but also as the medium of learning for visitors and other researchers in the same field.